Hubungan antara Social Support dengan Psychological Well Being pada Mahasiswa yang Memiliki Orang Tua Bercerai - Valen Mutiara Devia; Devi Rusli (Indo Publishing, 2025)
All humans want happiness, one of which is to have a harmonious family. However, not everyone can have a harmonious family because of the many family problems. One of the problems is the divorce of parents. Among those affected by divorce are children, especially adolescent children. One group of teenagers is students. This has an impact on the Psychological well-being of university students. Social Support is one of the factors affecting Psychological well-being. While undergoing college students did not receive support from the social environment. This phenomenon led researchers to see the relationship between Psychological well-being and Social Support in college students who experienced a family condition with their parents divorced. This study used a quantitative approach using correlational design. Sampling is performed using purposive sampling techniques. The data collection process involved the adaptation of Ryff (1989) and Cutrona and Russel (1987). Both scales show high reliability with coefficients 0.900 and 0.881, respectively. The findings of this study show a significant relationship between Social Support and Psychological well-being among students and divorced parents, as evidenced by a significance score of 0.00 (p <0.5). As a result, it can be concluded that Social Support is indeed linked to Psychological well-being.